Expansão canavieira e o uso da terra no estado de São Paulo - CAMARA, MARCIA REGINA GABARDO DA; CALDARELLI, CARLOS EDUARDO (Estudos Avançados, 2016)
The aim of this paper is to evaluate the expansion of sugarcane and its impacts on agricultural land use in the state of São Paulo between 1995 and 2013. A two-stage shift-share model was used, first to desegregate sugarcane production values in terms of area, productivity and price effects. Then, in a second stage, the model was used to evaluate the expansion of the planted area of sugarcane in terms of scale and substitution effects. The results showed that sugarcane has expanded in São Paulo, due especially to area and price effects, with low contribution of the productivity effect. This article concludes that sugarcane in São Paulo represents a land use conflict; it was corroborated by the high contribution of the substitution effect in sugarcane harvest.